2017
DOI: 10.4317/jced.53613
|View full text |Cite
|
Sign up to set email alerts
|

The all-on-four treatment concept: Systematic review

Abstract: ObjectivesTo systematically review the literature on the “all-on-four” treatment concept regarding its indications, surgical procedures, prosthetic protocols and technical and biological complications after at least three years in function.Study DesignThe three major electronic databases were screened: MEDLINE (via PubMed), EMBASE, and the Cochrane Library of the Cochrane Collaboration (CENTRAL). In addition, electronic screening was made of the ‘grey literature’ using the System for Information on Grey Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 63 publications
1
94
0
22
Order By: Relevance
“…For the nonrandomized studies, the studies were considered at low risk of bias in the case of Newcastle‐Ottawa Scale (NOS) scores of 7 stars or higher. (Soto‐Peñaloza, Zaragozí‐Alonso, Peñarrocha‐Diago, & Peñarrocha‐Diago, ) Among all the studies evaluated, both level I studies and 12 out of 20 level II studies showed high risk of bias (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…For the nonrandomized studies, the studies were considered at low risk of bias in the case of Newcastle‐Ottawa Scale (NOS) scores of 7 stars or higher. (Soto‐Peñaloza, Zaragozí‐Alonso, Peñarrocha‐Diago, & Peñarrocha‐Diago, ) Among all the studies evaluated, both level I studies and 12 out of 20 level II studies showed high risk of bias (Tables and ).…”
Section: Discussionmentioning
confidence: 99%
“…9 The "All-on-4" treatment concept was developed to maximize the use of the available residual bone in atrophic jaws, allowing immediate function and avoiding regenerative procedures (such as bone grafting) that increase treatment costs, patient morbidity, and complications inherent to these procedures. 18,19 Nevertheless, long term evidence of the All-on-4 treatment concept for the rehabilitation of the edentulous maxilla is lacking. 18,19 Nevertheless, long term evidence of the All-on-4 treatment concept for the rehabilitation of the edentulous maxilla is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…5,[11][12][13][14][15][16][17] The All-on-4 concept was further validated in the short and midterm outcomes considering the results of two systematic reviews that reported high survival rates in the rehabilitation of completely edentulous patients. 18,19 Nevertheless, long term evidence of the All-on-4 treatment concept for the rehabilitation of the edentulous maxilla is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants are a popular treatment option for patients that need to replace one tooth or more. Survival rates of dental implants are reported to be very high in the recent literature . These rates seem to indicate minimal complications with dental implants, however, careful consideration should be taken prior to implant placement as peri‐implantitis and other problems can be encountered .…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates of dental implants are reported to be very high in the recent literature. [1][2][3][4] These rates seem to indicate minimal complications with dental implants, however, careful consideration should be taken prior to implant placement as peri-implantitis and other problems can be encountered. 5,6 It is important to note the difference between implant survival and implant success.…”
mentioning
confidence: 99%